European Judo Championships: impact of the new rule changes on points and penalties - Franchini, E.; Takito, M. Y.; Calmet, M. (International Journal of Performance Analysis in Sport, 2013)
In 2013 the International Judo Federation started to test new rules to judo competitions with the objective of make judo more attractive for the general public and to promote which has been denominated "positive judo", i.e., a more combative style. The aim of the present investigation was to compare two consecutive European Judo Championships (2012 and 2013, i.e., before and after the rule changes, respectively) in terms of scores and penalties. Statistics involved chi-square, analysis for linear trends in proportions and odds-ratio (OR), using 5% as significance level. The rules changes resulted in the increase of penalties and in the decrease of waza-ari (males, X2=8.76, P=0.003, OR=0.55; females, X2=3.79, P=0.050, OR=0.61) and yuko (males, X2=38.93, P<0.001, OR=0.31; females, X2=6.84, P=0.009, OR=0.56) scores for both males and females, while increasing ippon only for males (X2=5.03, P=0.025). The total number of shido also increased for both groups (males, X2=14.21, P<0.001, OR=1.53; females, X2=6.63, P=0.010, OR=1.43), while the prevalence of hansoku-make increased only for males (X2=5.78, P=0.016, OR=8.43). Thus, the rules change did not achieve the goal established of increasing scores and decreasing penalties.